The Analysis of Women’s Representation in the House of Representatives of Central Java 2019-2024 - lbert J Rapha; Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2021)
The existence of women frequently perceived as “second sex” in society. In fact, their voices, ideas, and gender roles are often ignored. Thus, in order to support women’s right the United Nations through CEDAW encourages the achievement of 30% quota of women’s representation in legislative institution as the entrance of women’s interests in the policy-making process. Furthermore, the UN recommendation has been ratified by Indonesian government to produce the guidelines to spur women’s political participation through Ministerial Women Empowerment and Child Protection Regulation 07/2013 on Increasing Women’s Political Participation in Legislative. Nevertheless, the emergence of this affirmative policy has not been able to attain the target of least 30% representation in the legislative institution, including the House of Representatives of Central Java 2019-2024. Further, this research emphasizes about the factual condition of women’s political representation and why the women’s political representation enhancement policy still yet spur the women’s representation rate in the House of Representatives of Central Java 2019-2024. By using descriptive-qualitative method and System Theory basis, the author tries to scrutinize more deeply about the reality in the field based on four main factors: policy cognition, socio-culture, human resources, and political factor. According to the result, this research finds various hurdles on the policy implementation, including the deep rooted of patriarchy culture, the lack of women’s capability as policy makers, and various political factors.